Characterization of Research Nodes : An Integrative Approach Through Indexing - Das, K. K.; Bhattacharya, P. M.; Ghosh, A.; Dhar, T.; Pradhan, K.; Chowdhury, A. K.; Joshi, P. K.; Gathala, M. (International Journal of Bio-resource and Stress Management, 2016)
Appropriate understanding of situation is pre-requisite for effective implementation of a development programme or scheme. One of the serious drawbacks in failure of most of the developmental efforts (government, semi-government or non-government) is probably, poor understanding of the given situation. There are various parameters for characterising a situation and those (especially, the quantitative variables) are expressed in differential units too. The present study has been attempted to define/characterize research areas in terms of a unit free integrative approach namely, Farming System Index (FSI). This indexing approach is based on some defined scales on different variables. Development of FSI has been done by undertaking Focus Group Discussions in five nodes of Malda, a northern district in West Bengal. Data corresponds to agricultural year 2013−14. The selected nodes are characterised with the help of value of FSI which ranges from 0.51 to 0.59 which is indicative of the very fact that the village systems (i.e., node) lag substantially in development paradigm. Significance in difference among nodes with respect to various traits has been judged by following Kruskal-Wallis test followed by Bonferroni multiple comparison test. But, the source or cause of backwardness is not uniform in all the nodes. Accordingly prioritization of intervening issues has been done for each selected node which will be beneficial for effective implementation of future developmental programmes.